ANALISIS SALURAN DISTRIBUSI PRODUK CV. ADILA SNACK JAMBI - Eef Putra Jaya; Sissah Sissah; Agusriandi Agusriandi (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Distribution channels are channels used to distribute goods from producers to consumers. On CV. There are several factors at Adila Snack Jambi that can become obstacles in distribution, including the first human factor, where in distribution the company requires skilled humans or employees. The second is vehicles. Therefore, companies must prepare good vehicles so that distribution can run effectively. This research aims to find out how effective distribution channels are to increase the distribution of snacks at CV. Adila Snack Jambi, The benefits of this research are theoretically able to contribute ideas to the development of economics. It is hoped that the practical benefits can be used as information about distribution to increase sales. This type of research is field research which is descriptive qualitative in nature using primary and secondary data sources, interview and documentation data collection techniques and the analysis technique used is qualitative analysis using inductive thinking methods. The results of this research are that the distribution channel used by CV Adila Snack Jambi is a one-level channel. One level channel is a marketing intermediary between producers and consumers (CV Adila Snack Jambi and traders-consumers). The distribution strategy used by CV Adila Snack Jambi is intensive distribution, namely distributing products through as many channels and channel members (traders and outlets) as possible.